2014
DOI: 10.1038/gene.2014.72
|View full text |Cite
|
Sign up to set email alerts
|

Association of the LRRK2 genetic polymorphisms with leprosy in Han Chinese from Southwest China

Abstract: Leprosy is a chronic infectious and neurological disease that is caused by infection of Mycobacterium leprae (M. leprae). A recent genome-wide association study indicated a suggestive association of LRRK2 genetic variant rs1873613 with leprosy in Chinese population. To validate this association and further identify potential causal variants of LRRK2 with leprosy, we genotyped 13 LRRK2 variants in 548 leprosy patients and 1078 healthy individuals from Yunnan Province and (re-)analyzed 3225 Han Chinese across Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 49 publications
4
64
0
Order By: Relevance
“…We also found a significantly increased mtDNA copy number in lepromatous leprosy patients11 compared with controls. The mitochondrial outer membrane protein, LRRK2, has been identified by a genome-wide association study (GWAS) as one of the leprosy susceptibility genes in Han Chinese population12, and this was confirmed by our recent case-control study13 and other studies1415, although the associated LRRK2 SNPs or their effects were different in these studies. Most recently, we provided solid evidence to show that the OPA1 gene, encoding an mitochondrial inner membrane protein, was associated with leprosy susceptibility possibly by affecting mitochondrial function and antimicrobial pathways16.…”
supporting
confidence: 59%
See 3 more Smart Citations
“…We also found a significantly increased mtDNA copy number in lepromatous leprosy patients11 compared with controls. The mitochondrial outer membrane protein, LRRK2, has been identified by a genome-wide association study (GWAS) as one of the leprosy susceptibility genes in Han Chinese population12, and this was confirmed by our recent case-control study13 and other studies1415, although the associated LRRK2 SNPs or their effects were different in these studies. Most recently, we provided solid evidence to show that the OPA1 gene, encoding an mitochondrial inner membrane protein, was associated with leprosy susceptibility possibly by affecting mitochondrial function and antimicrobial pathways16.…”
supporting
confidence: 59%
“…Although there was no positive interaction among PARL, PINK1, OPA1 and LRRK2 SNPs (Table S6) based on our recently reported data1316 and current data, the positive associations of these four genes with leprosy suggested that mitochondrial related genes should play active roles in leprosy. The protein interaction network analysis supported this speculation, as we found that the other mitochondrial genes ( MCCD1, SDHD, SNCA , and VARS2 ) could interact with the reported leprosy susceptibility genes (Table S5).…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…Intriguingly, variation at the LRRK2 locus has also been connected by genome-wide association with immune diseases such as systemic lupus erythematosus (Zhang et al 2017), Crohn’s disease (Barrett et al 2008) and inflammatory bowel disease (Liu et al 2011) and with susceptibility to multibacillary leprosy (Wang et al 2015; Fava et al 2016). LRRK2 has also been linked to cancer, with the PD G2019S mutation associated with specific cancers such as non-skin and hormonal cancers (Agalliu et al 2015) and the R1441C mutation linked to increased risk of colon cancer (Tacik et al 2016).…”
Section: Lrrk2 In Diseasementioning
confidence: 99%